Rectangle-packing-based module placement - Murata, Hiroshi; Fujiyoshi, Kunihiro; Nakatake, Shigetoshi; Kajitani, Yoji (Proceedings of the 1995 IEEE/ACM international conference on Computer-aided design, 1995)
The first and the most critical stage in VLSI layout design is the placement, the background of which is the rectangle packing problem: Given many rectangular modules of arbitrary size, place them without overlapping on a layer in the smallest bounding rectangle. Since the variety of the packing is infinite (two- dimensionally continuous) many, the key issue for successful optimization is in the introduction of a P-admissible solution space, which is a finite set of solutions at least one of which is optimal. This paper proposes such a solution space where each packing is represented by a pair of module name sequences. Searching this space by simulated annealing, hundreds of modules could be successfully packed as demonstrated. Combining a conventional wiring method, the biggest MCNC benchmark ami49 is challenged.